EFEITO DA PLUVIOSIDADE SOBRE A FAUNA BENTÔNICA DO RIO XARQUINHO, GUARAPUAVA, PR - Scherer, Rodrigo (2013)
Benthic organisms are influenced by the prevailing environmental conditions of aquatic ecosystems, physical factors such as heavy rainfall, have the potential to cause degradation or distortion of the benthic community, this fact has been well studied in regions with distinct difference in rainfall in rainy season and drought and in studies of evaluating long periods of time, however, there are no studies that indicate the change that occurs in the benthic community after heavy rains, and in regions with rainfall distributed. The objective of this study was to evaluate the response of the benthic community to rainfall events of different magnitudes. Samples were collected at four points in Xarquinho River, located in the Araucaria Municipal Park and farm of enterprise Repinho. To collect benthic macroinvertebrates was used a collector Surber, organisms were screened in stereo-microscope and identified with keys for identification purposes. Comparison of community composition and evaluation of impacts suffered due to rain was held by ANOSIM tests, n-MDS and paired t test also been made classic descriptions ecological with the indices of Margalef, Shannon and Pielou. The description of the collect sites was performed by rapid habitat diversity evaluation protocol. 18 taxa were found in all samples. Chironomidae, Simuliidae and Hydropsychidae were the most abundant families, the high frequency of these groups is supported by the literature. Site samplings 1, 2 and 3 are similar to each other, according to the rapid habitat diversity evaluation protocol used in this study, however, point 4, is different from the sampling sites, this is corroborated by the composition of this community site that is statistically different according to analysis of ANOSIM. Ecological indicators used showed that the richness, diversity and equitability of the community sampled in this study is relatively small when compared with other studies, even though they have also been carried out in rivers of small order. According to tests n-MDS and ANOSIM, differences in benthic community before and after the rain, are not statistically significant, however, the paired t test, finds these same differences as significant, probably the paired t-test does not assess correctly the changes in the abundance of benthic fauna, which in some rain is positive and other is negative. The differences in community composition between samples are larger than the differences in community composition between sampling before and after the rain in the same collects, possibly periods of the year in which the collects were made have greatest potential for change in community composition than the peak flow checked.